Seleksi kelayakan nasabah penerima kredit dengan metode moora - Djesmedi, Dinda; Mellya Rindhani Aditia; Fitri Firdalius; Maharian Agung (Computer Science and Information Technology, 2024)
Electronics and furniture are now a necessity that is in great demand by the public. These products are chosen because they have various important functions in everyday life. The many benefits of electronics and furniture make many people want to have them. However, in reality, not everyone has enough funds to buy them. An alternative that is commonly used by the public is to take out credit, allowing them to have electronics and furniture without having to pay in full up front. However, the credit process is not as easy as a cash purchase, because there are a number of procedures that must be followed by the applicant. PT. Interyasa Mitra Mandiri faces several obstacles in assessing the eligibility of credit recipients which are still done manually, so it takes a long time to process the data. In this problem, the researcher uses four criteria that will be compared later, whether prospective consumers can be said to be eligible to receive credit, including collateral in the form of BPKB or other valuable documents that can be used if later there are problems with bad credit or others, type of work, income, and completeness of administration. Decision support systems have been widely applied in the fields of education, health, finance and even in the world of business and management. The working process of this decision support system greatly helps leaders in making decisions because the results obtained are more accurate because they are in accordance with the criteria of each interest. The purpose of the research conducted is to facilitate leaders in analyzing the feasibility of prospective electronic and furniture debtor customers using predetermined criteria, and to apply the Moora method as a method that can assist in the process of determining the feasibility of prospective customers who receive credit applications.